Bioremediation of polycyclic aromatic hydrocarbon in artificially contaminated soil / Nor Amani Filzah Mohd Kamil - Mohd Kamil, Nor Amani Filzah (Institute of Graduate Studies, UiTM, 2015)
Land used for industrial facilities or for waste disposal can be contaminated. Redevelopment of contaminated land often requires unacceptable risks are assessed and managed so that the site becomes suitable for its new use. One of the major criteria to be satisfied before such land can be reused is to ensure that remediation is carried out to remove all health hazards. One of the treatment methods that can be adopted involves bioremediation processes. Bioremediation process is considered to be environmentally sound and economically feasible. Other process, namely, physical and chemical processes require high energy, high costs and produce secondary contaminants that are more toxic if not completely degraded. This study is carried out to provide a better understanding on application of potential bacteria under non-indigenous condition, i.e., isolate from sludge and inoculate into contaminated soil. Many studies were conducted under indigenous and semi-indigenous condition. However, there are limited reports on studies under non-indiginous condition, particularly under aerobic condition. This study is also conducted to evaluate the effectiveness of potential bacteria and to established a mathematical model for PAHs biodegradation. The organic contaminants focus in this study is Polycyclic Aromatic Hydrocarbons (PAHs) and sand was selected as the soil media. PAHs are one of the most widespread organic contaminants and known to be highly toxic, mutagenic and carcinogenic. The objectives of this study are (i) a) establishment study parameters through characterization, (ii) biodegradation of PAHs, (iii) evaluation on effectiveness of PAHs biodegradation and (iv) model development…